2002
DOI: 10.1212/wnl.59.6.824
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, longitudinal diffusion tensor imaging study of brain injury in newborns

Abstract: MR diffusion images (for which contrast is determined by changes in D(av)) obtained on the first day after injury do not necessarily show the full extent of ultimate injury in newborn infants. Images obtained between the second and fourth days of life reliably indicate the extent of injury. By the seventh day, diffusion MR is less sensitive to perinatal brain injury than conventional MR because of transient pseudonormalization of D(av). Overall, diffusion MR may not be suitable as a gold standard for detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
143
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(161 citation statements)
references
References 28 publications
17
143
0
1
Order By: Relevance
“…ADC and RA were similar to that of controls, indicating that the measures normalized during the 10 days of normoxia. Normalization of ADC has been noted in both animal models subjected to varying mechanisms of injury (17,18) and human infants (19,20). Although this acute reduction in ADC after injury is related to physiologic (not structural) changes, the subsequent pseudonormalization is likely due to structural changes associated with lower tissue cell density.…”
Section: Discussionmentioning
confidence: 97%
“…ADC and RA were similar to that of controls, indicating that the measures normalized during the 10 days of normoxia. Normalization of ADC has been noted in both animal models subjected to varying mechanisms of injury (17,18) and human infants (19,20). Although this acute reduction in ADC after injury is related to physiologic (not structural) changes, the subsequent pseudonormalization is likely due to structural changes associated with lower tissue cell density.…”
Section: Discussionmentioning
confidence: 97%
“…3 For future infants with VGAM, we intend to perform MRI with diffusion weighted images about 24-48 h after each endovascular procedure. 30 This may provide information as to which procedure was responsible for any resulting cerebral infarction, and may enable alterations to the timing of procedures, the number of feeding arteries to be embolized or to the materials used for embolization (metal coils and/or NBCA-lipiodol glue).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Results have provided further understanding of pathogenesis and treatment in a range of neurologic disorders by providing visualization of specific white matter fiber tracts (see review by Horsfield and Jones 22 ). [23][24][25][26][27] Although injury to the corticospinal tracts is thought to be the major determinant of motor impairment in children with PVL, recent studies have shown that sensory pathways, including the posterior thalamic radiation, may be affected instead or, concurrently, 28 indicative of the complexity of white matter involvement in PVL.…”
mentioning
confidence: 99%